Using Interpersonal Dimensions of Personality and Personality Pathology to Examine Momentary and Idiographic Patterns of Alliance Rupture - Luo, Xiaochen; Hopwood, Christopher J.; Good, Evan W.; Turchan, Joshua E.; Thomas, Katherine M.; Levendosky, Alytia A. (Frontiers in Psychology, 2021)
The Alternative Model of Personality Disorders (AMPD) integrates several theoretical models of personality functioning, including interpersonal theory. The interpersonal circumplex dimensions of warmth and dominance can be conceptualized as traits similar to those in AMPD Criterion B, but interpersonal theory also offers dynamic hypotheses about how these variables that change from moment to moment, which help to operationalize some of the processes alluded to in AMPD Criterion A. In the psychotherapy literature, dynamic interpersonal behaviors are thought to be critical for identifying therapeutic alliance ruptures, yet few studies have examined moment-to-moment interpersonal behaviors that are associated with alliance ruptures at an idiographic level. The current study examined the concurrent and cross-lagged relationships between interpersonal behaviors and alliance ruptures within each session in the famous Gloria films (“Three Approaches to Psychotherapy”). Interpersonal behaviors (warmth and dominance) as well as alliance ruptures (i.e., withdrawal and confrontation) were calculated at half minute intervals for each dyad. We identified distinct interpersonal patterns associated with alliance ruptures for each session: Gloria (patient)’s warmth was positively related with withdrawal ruptures concurrently in the session with Carl Rogers; Gloria’s dominance and coldness were related with increased confrontation ruptures in the session with Fritz Perls concurrently, while her coldness was also predicted by confrontation ruptures at previous moments; lastly, both Gloria’s dominance and Albert Ellis’s submissiveness were positively related with withdrawal ruptures. These interpersonal patterns demonstrated the promise of using AMPD dimensions to conceptualize momentary interpersonal processes related to therapy ruptures, as well as the clinical importance of attuning to repetitive, dyad-specific interpersonal cues of ruptures within each session.